Factorization of the Popov function of a multivariable linear distributed parameter system in the non-coercive case: A penalization approach - Pandolfi, Luciano (Zielona Góra: Uniwersytet Zielonogórski)
We study the construction of an outer factor to a positive definite Popov function of a distributed parameter system.
Keywords: linear distributed systems; dissipative systems; factorization; outer factor; Popov function